Effects of generally recognized as safe (GRAS) and dietary compounds on phenylephrine metabolism in LS180 human intestinal cells. (18th November 2018) - Zhang, Zhenxian; Gerk, Phillip M.
Abstract: Phenylephrine (PE) has low and variable oral bioavailability in humans, due in part to presystemic metabolism by sulfation. LS180 cells were used as a model of the human intestinal epithelium to examine phenylephrine metabolism and its inhibition by generally recognized as safe (GRAS) and dietary compounds. Curcumin, zingerone, resveratrol, guaiacol, pterostilbene and isoeugenol significantly inhibited phenylephrine disappearance, while vanillin, propylparaben and eugenol did not. However, when propylparaben was combined with either vanillin or eugenol, the phenylephrine disappearance was significantly inhibited. These data suggest that these compounds or combinations thereof may have potential to improve phenylephrine oral bioavailability.